2011
DOI: 10.1158/1078-0432.ccr-10-1891
|View full text |Cite|
|
Sign up to set email alerts
|

Pancreatic Tumor Suppression by Benzyl Isothiocyanate Is Associated with Inhibition of PI3K/AKT/FOXO Pathway

Abstract: Purpose: Our previous studies have shown that benzyl isothiocyanate (BITC) suppress pancreatic cancer growth by inducing apoptosis but the molecular mechanism was unclear. In this study we hypothesized the involvement of PI3K/AKT/FOXO pathway in BITC-induced apoptosis.Experimental Design: Mice were implanted BxPC-3 tumor xenografts and orally gavaged with 12 mmol BITC. Plasma and tumor BITC concentration was estimated by liquid chromatography/tandem mass spectrometry. BxPC-3 and PanC-1 cells were used to eluci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
138
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(143 citation statements)
references
References 43 publications
3
138
1
1
Order By: Relevance
“…FOXO1 protein is implicated in diverse cellular activities including DNA repair, oxidative stress resistance, and apoptosis [31,32]. Moreover, enhanced FOXO1 transcription activity is required to promote apoptosis and cell cycle [33]. CCAAT/enhancer binding protein beta (C/EBPb) is a transcription factor belonging to C/EBPs, which all have a highly conserved, basic leucine zipper domain at the C-terminus involved in dimerization and DNA binding [34].…”
Section: Discussionmentioning
confidence: 99%
“…FOXO1 protein is implicated in diverse cellular activities including DNA repair, oxidative stress resistance, and apoptosis [31,32]. Moreover, enhanced FOXO1 transcription activity is required to promote apoptosis and cell cycle [33]. CCAAT/enhancer binding protein beta (C/EBPb) is a transcription factor belonging to C/EBPs, which all have a highly conserved, basic leucine zipper domain at the C-terminus involved in dimerization and DNA binding [34].…”
Section: Discussionmentioning
confidence: 99%
“…The gene category Wnt signaling pathway, has been reported to be involved in metastasis of pancreatic carcinogenesis (25), and the gene category MAPK signaling pathway has been shown to participate in the progression of pancreatic cancer though multiple mechanisms (26)(27)(28)70). The gene categories FoxO signaling pathway have been reported to suppress or activate pancreatic cancer progression by different drugs or compound (29,30). The gene categories 'Ubiquitin mediated proteolysis' participates in pancreatic cancer cell growth in vitro and in vivo (31).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the effects of anticancer agents may be regulated through activation of FOXO transcription factors (41)(42)(43). In addition to their effects on cell cycle, apoptosis, differentiation and reactive oxygen species, FOXO proteins have also been implicated in the negative regulation of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%